PERAN EKSTRAKURIKULER PRAMUKA DALAM MEMBENTUK SIKAP NASIONALISME DAN PATRIOTISME PADA SISWA DI SMP 17 MATARAM - Ririn Abaitusiva; Rispawati; Bagdawansyah Alqadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Scout extracurricular activities are also mandatory extracurricular activities for students from elementary school to high school. Scout extracurricular activities are activities carried out outside of the subject that aim to develop the interests, talents and potential of each student. This study aims to determine the implementation of scout extracurricular activities at SMP Negeri 17 Mataram and to determine the role of scout extracurricular activities in shaping the attitude of nationalism and patriotism of students at SMP Negeri 17 Mataram. This study uses a qualitative type with a descriptive approach. The subjects in this study include the Principal, Scout Leader, PPKn Teacher of SMPN 17 Mataram. Data collection techniques in this study use observation, interview and documentation techniques. After the data is collected, it is analyzed using data reduction, data presentation and conclusion drawing. The results of the study show that the implementation of scout extracurricular activities at SMP 17 Mataram consists of three aspects of activities which include: planning scout activities, implementing scout extracurricular activities and materials and forms of scout activities. In the aspect of scouting activity planning, it consists of preparing work programs, determining schedules, and determining activity objectives. Aspects of the implementation of scouting extracurricular activities include: routine training activities, and the role of scout leaders. Then finally on the material aspects and forms of scouting activities which include: basic scouting skills, survival skills, and discipline and leadership. The role of scouting extracurricular activities in shaping nationalism and patriotism. Nationalism consists of several aspects including: Flag ceremonies and respect for national symbols, Marching activities and ceremonial procedures, Camping (Persami, Perjusa, Large camping), Scout competitions (LT, Pioneering, Senaphore, Smart Agility) and Appreciation of Heroic Character Values. Patriotism includes: Participation in Commemorating National Holidays, Maintaining Cleanliness and Sustainability of the School Environment, Discipline and Responsibility in Scouting Activities, Maintaining Unity and Respecting Differences, Maintaining being an Indonesian nation and Willing to Sacrifice for the Common Good. Keywords: Scouting Extracurricular Activities; Nationalism; Patriotism